a) y+6x=5 if x= -1 then y+6(-1)=5 then y = 11
b) same thing if x = 3 then y+6(3)=5 y+18=5 subtract both sides by -18 and leave y on left then add 5+(-18)= 13 then y=13
B same as above
question (a) asks you to solve for y because x is -2
(b) asks you to solve for x because y is known
3x+2y=-6 if y = 3 you write 3x+2(3)=-6 3x+6=-6 move the +6 over to right side by subtracting 6 from both side 3x=-6 + -6 so 3x=-12 to get rid of the 3 and only leave the x you want to divide both side by 3 then x= -12/3 then the answer would be x=-4
How about this?